The Role of Organizational Commitment in Mediating the Effect of Job Satisfaction and Compensation on Employee Performance at The Ongan & Kimi Sushi - Anak Agung Istri Winda Novitasari; Ida Bagus Udayana Putra (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
This research aims to analyze the role of organizational commitment in mediating the effect of job satisfaction and compensation on employee performance at the Ongan & Kimi Sushi. The sample in this research is the entire population of 30 people. This research uses a Likert scale to measure variables when testing the validity and reliability of variables. Data collection techniques used in this research are observation, interviews, and surveys. This research uses Partial Least Square (PLS) analysis. The results of the research indicate (1) job satisfaction has a positive and significant effect on organizational commitment, (2) compensation has a positive and significant effect on organizational commitment, (3) job satisfaction has a positive and significant effect on employee performance, (4) compensation has a positive effect and significant effect on employee performance, (5) organizational commitment has a positive and significant effect on employee performance, (6) organizational commitment does not mediate the relationship between job satisfaction and employee performance, and (7) organizational commitment partially mediates the relationship between compensation and performance employee.